EXARC visits Moscow - Milica Tapavički-Ilić; Artūrs Tomsons (EXARC Journal)
Between the 1st to the 12th of June 2017, a huge festival called "Times and Epochs" (Времена и эпохи - Cобрание) was organized in Moscow. This was the occassion to gather participants not only from Russia, but also from many other countries, and demonstrate the best of reenactment to festival visitors. Two EXARC members, Milica Tapavicki-Ilic (also the EXARC board member) and Arturs Tomsons attended the festival to present and promote EXARC, but also to experience such a significant festival.